PENERAPAN MODEL PEMBELAJARAN KONSTRUKTIVISME UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA di SD - Windurat Iriyanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2014)
The background of this study on students' ability to solve any math problem that the teacher always gets a low value (at 51), this is caused by the learning model used is less varied and lack of active participation of the students. So that learners absorption of any material submitted by teachers is unacceptable to the maximum by learners. This study has been able to answer hipoteses